The leadership odyssey: It$1 (Bs not easy to become less directive and more empowering. Here$1 (Bs how to navigate the challengess - Lbarra, H., Hildebrand, C. A. and Vinck, S. (Harvard Business Review)
A paradox of business is that while leaders often employ a hands-on, directive style to rise to the top, once they arrive, they$1 (Bre supposed to empower and enable their teams. Suddenly, they$1 (Bre expected to demonstrate (3z(Bpeople skills.(3y (BAnd many find it challenging to adapt to that reality.- Reproduced s